Simulated Wear and Fatigue Performance of Cobalt–Chrome–Molybdenum and Co–Cr–Free Nitrided Titanium Femoral Components in Primary Total Knee Arthroplasty - Ramos, Michael S.; Mimnaugh, Kimberly D.; Khan, Shujaa T.; Orozco-Villasenor, Diego A.; Schultz, Mackenzie; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2025)
Cobalt–chromium–molybdenum (Co–Cr–Mo) femoral components are widely used in total knee arthroplasty (TKA) due to their mechanical strength and wear performance. However, concerns regarding corrosion, metal ion release, and hypersensitivity have prompted the development of alternative materials, including nitrided titanium–aluminum–vanadium (nTi–6Al–4V). This study aimed to compare the simulated wear performance of Co–Cr–Mo and nTi–6Al–4V femoral components when articulated against conventional polyethylene articular surface bearings and evaluate the fatigue performance of nTi–6Al–4V components. In vitro wear testing, per ISO 14243-3, was conducted for 5 million cycles (Mc) using posterior-stabilized Persona Primary knee system femoral components manufactured from Co–Cr–Mo and nTi–6Al–4V coupled with conventional ultra-high-molecular-weight polyethylene articular surfaces. Mean steady-state wear rates (mg/Mc) of the articular surface bearings were gravimetrically determined. Surface roughness (Ra) measurements of the femoral components and the articulating surfaces were captured using a contacting stylus profilometer. Polyethylene wear debris morphology was also analyzed. Two fatigue loading scenarios (cantilever loading and three-point bend) of the posterior condyles of femoral components were completed for 10 Mc. The mean steady-state wear rate of the nTi–6Al–4V bearing couple (17.0 ± 1.8 mg/Mc) was noninferior to the Co–Cr–Mo bearing couple (22.8 ± 6.7 mg/Mc). No statistically significant differences were found in the Ra measurements of femoral components or articular surfaces before and after 5.0 Mc (p = 0.21). No statistical difference in polyethylene debris morphology was observed between components (p = 0.07). In both fatigue loading scenarios, no fracture or cracking of the nTi–6Al–4V femoral components occurred. The Co–Cr–Mo and nTi–6Al–4V bearing couples performed similarly regarding mean steady-state wear rates, Ra measurements, and debris morphology in simulated wear conditions. These results provide insights into the wear properties of Co–Cr free femoral TKA components. Additionally, the nTi–6Al–4V components met the performance requirements related to posterior condyle fatigue strength. Further clinical studies are needed to confirm these in vitro findings.
Keywords: cobalt–chromium–molybdenum; nitrided titanium–aluminum–vanadium; total knee arthroplasty; wear performance